Upaya Peningkatan Kesehatan Ibu Hamil Melalui Prenatal Yoga Ibu Hamil TM III untuk Menurunkan Tingkat Kecemasan dalam Menghadapi Proses Persalinan di PMB Sri Rejeki DH Jabung Tanon Plupuh Sragen - Hutari Puji Astuti; Yunia Renny Andhikatias (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Women who experience anxiety during pregnancy will experience more abnormal labor and can even be complicated by maternal and fetal death. Psychological conditions with anxiety and depression in pregnant women will affect the emergence of diseases and complications of pregnancy and childbirth, both in the mother and the baby. Anxiety in pregnancy has been proven to be reduced through physical exercise. One of the recommended physical exercises is yoga because it is low cost, easy to do and very beneficial for physical and psychological fitness. Yoga in pregnancy is more effective in reducing anxiety and depression, because in yoga in addition to doing physical exercise, pregnant women are equipped with positive affirmations so that mothers can accept physiological changes during pregnancy and childbirth.The general objective of this activity is that pregnant women at PMB Sri Rejeki DH Jabung Tanon Plupuh Sragen understand and can do prenatal yoga independently. The method of this activity is carried out by lecture, namely the method used as an introduction to provide knowledge about prenatal yoga for pregnant women in Trimester III and with discussion and questions and answers, as well as practice or demonstration of prenatal yoga for pregnant women. The media used is a poster of prenatal yoga for pregnant women in Trimester III. The conclusion of the community service activity is that pregnant women have understood about prenatal yoga to reduce anxiety levels in facing the labor process. This can be seen from the results of the pre-test and post-test, where before the counseling and practice of prenatal yoga, pregnant women did not understand several things about prenatal yoga by 40%. However, after the counseling, pregnant women became more knowledgeable about prenatal yoga, namely 90%. The results of this community service activity are that pregnant women can do prenatal yoga independently at home, where before the prenatal yoga training, pregnant women were not able to do prenatal yoga independently. Some pregnant women have reduced their anxiety after doing prenatal yoga with several independent implementations at home, with the help of prenatal yoga videos.